KARAKTERISTIK PERMUKIMAN KUMUH DI SEPADAN SUNGAI INDRAGIRI, RENGAT, RIAU - Aldy, Pedia; Dharma S, Mira (Talenta Publisher, 2017)
Rengat, a capital of Kabupaten Indragiri Hulu, is a developing city in Riau. Development of the city was followed by increasing of population and growth of housing and residential area. Growth of housings and residential area in Rengat City are along Sungai Indragiri. Along this river, housings and residential area have degradation quality and disordered pattern. The purpose of this research was to identify the characteristic of slums area along Indragiri’s river. There are 6 Desa (villages) which are been taken to this study, namely Desa Kuantan Baru (industry area), Desa Kuantan Baru, Desa Kampung Dagang, Desa Kampung Besar Kota, Desa Pasar Kota and Desa Sekip Hulu. This research used criteria parameter assessment for slums area. The criteria consist of: non-economic vitality criteria, economy area vitality criteria, land ownership, infrastructures and facilities, and government commitment. This research finding that from 6 villages, Desa Kampung Besar Kota is a slums area, based on parameter assessment. Property Development approach was conducted to handling slums area of Desa Kampung Besar.